2020
DOI: 10.1002/pa.2538
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the dynamic impact of external debt on economic growth in Nigeria: Cointegration and conditional causality analysis

Abstract: This study examines the dynamic effects of external debt stocks on real economic growth in Nigeria—incorporating debt services, interest rate, inflation, and capital formation. The study utilizes annual time series from 1981 to 2017 employing the dynamic autoregressive distributed lag (ARDL) cointegration bounds test methodology. Empirical findings indicated that external debt stocks and debt services have a significant effect on real economic growth both in the short and long run. The result of the pairwise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The Neo-Classical theory argued that budget deficit and borrowing is harmful and countries should practice system of balanced budgeting (Lwanga & Mawejje, 2014). Faizulayev et al (2020) stated that the neoclassical economic growth model posits external debt arises when capital-constraint countries seek for borrowing abroad.…”
Section: Theoretical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Neo-Classical theory argued that budget deficit and borrowing is harmful and countries should practice system of balanced budgeting (Lwanga & Mawejje, 2014). Faizulayev et al (2020) stated that the neoclassical economic growth model posits external debt arises when capital-constraint countries seek for borrowing abroad.…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…Didia & Ayokunle (2020) provided evidence that in the short-run and the long-run, external debts have positive relationship with the Nigerian economy but not statistically significant. Faizulayev et al (2020) used data from 1981 to 2017 in their study. The result showed that debt services and external debt have a negative and significant effect on real growth.…”
Section: Empirical Reviewmentioning
confidence: 99%